Jonathan Edwards, the Gospel of John, and the Glory of God - Waters, Guy Prentiss 1975- (2025)
The glory of God is a leading motif in the Fourth Gospel. It also holds a prominent role in the writings of Jonathan Edwards. This article explores the way in which Edwards read texts from the Gospel of John relating to the glory of God. It shows how Edwards defines God’s glory from John’s Gospel, and how Edwards explores the ways in which John testifies to the manifestation of the glory of God across redemptive history.
Keywords: Fourth Gospel; Glory of God; Gospel of John; Jonathan Edwards; Puritan; history of interpretation